A Novel UHPLC-MS/MS Method for Measuring 8-iso-Prostaglandin F2α in Bronchoalveolar Lavage Fluid - Holder, Cory; Adams, Aaron; Allison, Claire; Cote, Olivia; Lippens, Rachel; Blount, Benjamin C; Wang, Lanqing (Frontiers in Chemistry, 2021)
In August 2019, the Centers for Disease Control and Prevention (CDC) received the first reports of lung injuries that were eventually termed e-cigarette, or vaping, product use–associated lung injury (EVALI). As part of the investigation, CDC laboratories rapidly developed assays for analyzing substances in bronchoalveolar lavage (BAL) fluid collected from EVALI case patients. This report describes the development and validation of a high-throughput isotope dilution UHPLC-MS/MS method for measuring a major oxidative stress biomarker, 8-iso-prostaglandin F2α (8-isoprostane), in BAL fluid samples. The method showed good sensitivity, 17.6 pg/mL LOD, and requires only 50 μL of sample volume. The method had high throughput with an analytical run time of 11 minutes. The within-day and between-day coefficient of variation (CV) were below 2%. Accuracy, calculated from spiked recovery, at three spiking levels, ranged from 95.5 - 101.8%. This novel UHPLC-MS/MS method characterizes oxidative stress in lung epithelial tissue and thus helps to elucidate potential pathologic processes.